Effects of Inoculants (Chlorobium limicola and Rhodopseudomonas palustris) on Cucumber (Cucumis sativus L.) Seedlings in Stimulating their Nutrient Uptake and Growth - Shuang, Shao; Dongdong, Wang; Dan, Zhu (Journal of Nutritional Therapeutics, 2017)
Rhizobacteria-containing biofertilizers are perfect tools to promote plant growth for the superiority of reducing environmental damages. Two strains of Chlorobium limicola and Rhodopseudomonas palustris were applied in the experiment as potential inoculants for cucumber seedlings. Significant enhancement in the availability of macronutrient elements N, P and K were observed in soils, and further improvement in their uptake was also obtained in cucumber plants. Accumulation of essential micronutrients Fe and Zn were detected both in the roots and shoots. The two strains increased chlorophyll and carotinoid synthesis, plant height, stem diameter, wet weight and dry weight. Various doses had significant effects on plant growth stimulation, C. Limicola with 107 cells mL-1 and R. Palustris with 108 cells mL-1 seem to be better on the whole.